Reciprocial movements of endodontic files: Simpler and more certain therapeutic procedure - Živković Slavoljub; Popović-Bajić Marijana; Živković Marija (Serbian Medical Society - Dental Section, Belgrade, 2022)
Numerous technological solutions in recent years have significantly improved the cleaning and shaping of canals and made canal instrumentation simpler, more efficient and safer. Significantly faster and less stressful canal instrumentation for the therapist is enabled by the specific design of the file working part and a special thermal modification of NiTi alloy with a change in the movement dynamics of the file in the canal. Research has shown that the problem of cyclic fatigue and torsional stress of the file during canal preparation can be solved by changing usual continuous rotation of the file. Dental technology has introduced the technique of reciprocal movements as an alternative to full file rotation. This change in file rotation direction during instrumentation, based on the technique of balanced forces, significantly reduces contact surface with the canal wall, eliminates the effect of screwing, extends the life of the file and further increases safety of instrumentation of different canal systems. An important advantage of changing the usual dynamics of file movements is that the concept of reciprocal movements is based on the use of only one file, which in addition to shortening treatment time also makes this intervention safer and with significantly lower percentage of defects and fractures of NiTi files. The aim of this paper was to present the concept of canal instrumentation with NiTi files with reciprocal movements as well as development, properties and possibility of application of these files in different clinical situations.